Development of Hypercontent-Based Probability Teaching Materials with Problem-Based Learning Model (Unnes Journal of Mathematics Education, 2022)
This research focuses on developing hypercontent-based Probability teaching materials based on problem-based learning models. The purpose of this study was to determine the characteristics, feasibility, and readability of hypercontent-based teaching materials. This type of research is Research and Development (R&D). The procedure used in this research and development adopts the modified Sugiyono (2015) development model, namely (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product trial, and (7) product revision. This research produces a hypercontent-based Probability teaching material based on a problem-based learning model that has met the suitability of characteristics. The teaching materials were declared valid and suitable for use in learning mathematics with an average feasibility score of 85.82%. Based on the readability test, it was found that the hypercontent-based Probability teaching materials were easy to understand and could be used independently by students with an average readability score of 79.91%.